2013
DOI: 10.1002/eat.22150
|View full text |Cite
|
Sign up to set email alerts
|

Functional neuroanatomy of body checking in people with anorexia nervosa

Abstract: This preliminary study with modest power suggests that AN patients have reduced activation in cortical areas associated with self-reference, body action perception, and social cognition in females with AN.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 43 publications
1
18
1
1
Order By: Relevance
“…Told to process images in a self-referring wayFladung et al, 2010 [24]AN = 14HC = 14DSM-IV16.4 (1.8)24.4 (7.6)Examine the ventral striatal system in adults with ANIncreased activity in the ventral striatum to underweight stimuliView images of underweight, normal weight and overweight bodies, estimate body weight, and process stimuli in a self-referring wayFladung et al, 2013 [25]AN = 13HC = 14DSM-IV16.6 (1.2)16.0 (1.1)Examine the ventral striatal system in adolescents with ANIncreased activity in the ventral striatum to underweight stimuliViewing normal size and distorted pictures of own bodyCastellini et al, 2013 [21]AN = 18HC = 19DSM-IV16.1 (1.4)24.7 (7.6)Explore neural network activated by processing of own bodyIncreased activity in the inferior frontal gyrus and middle temporal gyrus when viewing oversized imagesView images of idealized women, and compare with selfFriederich et al, 2010 [26]AN = 17HC = 18DSM-IV15.6 (1.4)24.9 (5.6)Investigate neural correlates of body dissatisfactionIncreased activation in the insula and premotor cortex, decreased activity of the rostral anterior cingulate cortexNegative words concerning body imageMiyake et al, 2010 [27]AN-R = 11AN-BP = 11HC = 11DSM-IVAN-R:15.2 (2.1)27.0 (9.0)AN-BP:15.5 (1.6)27.2 (4.8)Investigate functional abnormalities during processing of negative words concerning body imageIncreased activity in the amygdala in both AN-R and AN-BP than in BN and controls, increased ventromedial prefrontal cortex in AN-BP and BN than in controls, and increased activity in the inferior parietal lobe in AN-R and AN-BP than controlsBody and appearance (cont. )Viewing images of body checkingSuda et al, 2013 [28]AN = 20HC = 15DSM-IV15.7 (1.0)27.0 (7.5)Investigate brain activation to images of body checkingReduced activation of the anteromedial prefrontal cortex and fusiform gyrusViewing images of faces and houses at different spatial frequenciesLi et al, 2015 [30]AN-REC = 15HC = 15BDD = 15DSM-IV20.4 (1.6)23.6 (3.5)Investigate visual and visuospatial processing in AN and body dysmorphic disorder (BDD)Both groups had increased activation in secondary visual processing regions and dorsal visual streamNeuropsych functionsEmbedded figures testFonville et al, 2013 [31]AN = 35HC = 35DSM-IV1...…”
Section: Main Textmentioning
confidence: 99%
See 1 more Smart Citation
“…Told to process images in a self-referring wayFladung et al, 2010 [24]AN = 14HC = 14DSM-IV16.4 (1.8)24.4 (7.6)Examine the ventral striatal system in adults with ANIncreased activity in the ventral striatum to underweight stimuliView images of underweight, normal weight and overweight bodies, estimate body weight, and process stimuli in a self-referring wayFladung et al, 2013 [25]AN = 13HC = 14DSM-IV16.6 (1.2)16.0 (1.1)Examine the ventral striatal system in adolescents with ANIncreased activity in the ventral striatum to underweight stimuliViewing normal size and distorted pictures of own bodyCastellini et al, 2013 [21]AN = 18HC = 19DSM-IV16.1 (1.4)24.7 (7.6)Explore neural network activated by processing of own bodyIncreased activity in the inferior frontal gyrus and middle temporal gyrus when viewing oversized imagesView images of idealized women, and compare with selfFriederich et al, 2010 [26]AN = 17HC = 18DSM-IV15.6 (1.4)24.9 (5.6)Investigate neural correlates of body dissatisfactionIncreased activation in the insula and premotor cortex, decreased activity of the rostral anterior cingulate cortexNegative words concerning body imageMiyake et al, 2010 [27]AN-R = 11AN-BP = 11HC = 11DSM-IVAN-R:15.2 (2.1)27.0 (9.0)AN-BP:15.5 (1.6)27.2 (4.8)Investigate functional abnormalities during processing of negative words concerning body imageIncreased activity in the amygdala in both AN-R and AN-BP than in BN and controls, increased ventromedial prefrontal cortex in AN-BP and BN than in controls, and increased activity in the inferior parietal lobe in AN-R and AN-BP than controlsBody and appearance (cont. )Viewing images of body checkingSuda et al, 2013 [28]AN = 20HC = 15DSM-IV15.7 (1.0)27.0 (7.5)Investigate brain activation to images of body checkingReduced activation of the anteromedial prefrontal cortex and fusiform gyrusViewing images of faces and houses at different spatial frequenciesLi et al, 2015 [30]AN-REC = 15HC = 15BDD = 15DSM-IV20.4 (1.6)23.6 (3.5)Investigate visual and visuospatial processing in AN and body dysmorphic disorder (BDD)Both groups had increased activation in secondary visual processing regions and dorsal visual streamNeuropsych functionsEmbedded figures testFonville et al, 2013 [31]AN = 35HC = 35DSM-IV1...…”
Section: Main Textmentioning
confidence: 99%
“…Negative words related to body image elicited increased amygdala, medial prefrontal cortex and inferior parietal lobe activation [27]. Finally, one study found reduced activation of the prefrontal cortex and fusiform gyrus to images of body checking behavior [28]. Body checking involves repetitive checking of body shape and weight, and is a common feature of AN [29].…”
Section: Main Textmentioning
confidence: 99%
“…Further, the amount of alexithymia in the AN group correlated with the activation of both the anterior and posterior cingulate cortex, suggesting that emotional processing of negative stimuli in these self-referential neural regions may be specifically impaired in AN. Suda et al 109 also observed reduced activation in the medial prefrontal cortex and right fusiform gyrus in an AN group, in response to viewing individuals engaging in body checking, an ED behavior. All of these studies suggest that self-knowledge may be specifically altered in EDs, consistent with the recently proposed idea that our self may be largely defined by what is rewarding to us.…”
Section: Resultsmentioning
confidence: 93%
“…During inhibitory control paradigms, individuals with BN and BED exhibit insufficient engagement of neural circuits involved in cognitive control [54,55], which may indicate general self-regulation impairments. Alterations in neural regions associated with self-referential processing, somatosensory processing, perception of body stimuli, and affective processing may underlie body image distortions observed among individuals with AN and BN [49,[56][57][58][59].…”
Section: Neurobiological Ed Risk Factorsmentioning
confidence: 98%